Impact of Legal Incentives on “Credit Fraud” Criminal Offence - Balla, Rezana; Elezi, Alketa (European Journal of Multidisciplinary Studies, 2021)
Currently, the number of financial institutions has been increased in Albania, which provides Albanian citizens with access to various financial services, mainly to obtain financing services in the form of microcredit. Given the history of our people, not all the Albanian citizens have had opportunity to have access and to benefit from various financial services. Denial of financial services is an issue that has affected not only Albania, but also other small Balkan countries. The reasons for this denial are numerous, but among them, we can distinguish the lack of lending experience, as one of the common reasons for being excluded in these countries from the development of the financial sector. Taking into consideration that, the growth of financial institutions led to the growth of financial services by raising awareness and financial education of citizens. Finally, the Bank of Albania[1], as the supervisor of financial activities, intends to set a ceiling on the interest of consumer loans provided by non-bank financial institutions and commercial banks in Albania. This paper aims to present through a professional legal treatment all the challenges of the legal and institutional framework of the Bank of Albania, itself in undertaking this initiative. The questions we intend to answer through this paper are: Is the Bank of Albania legitimized to set a ceiling interest rate for consumer credit? What are the benefits or challenges that this initiative will bring to the financial sector? How will this regulation affect the criminal offense of "Credit Fraud"? How will the financial industry be designed after the implementation of the initiative? Will it have any impact on customer beneficial? etc. [1] Bank of Albania is the Central Bank in Albania and has the supervising authority over second rank tier of banking system and the entire financial system.